PENERAPAN MODEL PEMBELAJARAN KOOPERATIF POE (Predict, Observe, Explain) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TERMOKIMIA DI KELAS XI IPA SMA NEGERI 9 PEKANBARU - Suzana '; Erviyenni '; R. Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to increase student achievement by application ofcooperative learning model POE (Predict, Observe, Explain) on learning topic ofthermochemical in XI IPA SMA N 9 Pekanbaru. This is an experimental research withrandomized control group pretest-posttest design. Subject of this research are XI IPA 4as the experimental class, XI IPA 3 as the control class which were determinedrandomly after conducting normality and homogeneity test. The experimental groupwas treated with the application of cooperative learning model POE (Predict, Observe,Explain) while the control group without the application cooperative learning modelPOE (Predict, Observe, Explain). The data analysis to test the hypothesis was using ttestright side. Based on the data analysis, it is obtaine tcount = 3,53 and ttable = 2,00 withα=0,05, dk = 73, tcount > ttable is 3,53 > 2,00, It’s mean that the application ofcooperative learning model POE (Predict, Observe, Explain) can improve studentsachievement on the subject of thermochemical in XI IPA SMA Negeri 9 Pekanbaru. Theraising student achievement category in the experimental class including a high scoreby normalized gain of 0,77.Keywords: Cooperative learning, learning model POE (predict, Observe, Explain),constructivism, learning achievement